Acute Aortic Dissection in Pregnancy in a Woman with Undiagnosed Marfan Syndrome - Mandana Master; Gavin Day (Hindawi Limited, 2012)
We report a case of acute aortic dissection in a lady of 28 weeks of gestation with undiagnosed Marfan syndrome. The patient had been seen in our antenatal clinics. Her history documented in her pregnancy record was negative for genetic/congenital abnormalities. There was no family history documented. Subsequently, at 28 weeks of gestation, the patient presented with sudden onset chest, jaw, and back pain. Further history revealed that her father had died at the age of 27 of an aortic dissection. Echocardiography showed aortic root dissection with occlusion of aortic branches. She subsequently underwent an emergency lower segment caesarean section followed by surgical repair of type A dissection. A simultaneous type B dissection was managed conservatively. On later examination, our patient fulfilled the diagnostic criteria for phenotypic expression of Marfan syndrome. Genetic testing also confirmed that she has a mutation of the fibrillin (FBN 1) gene associated with the disease.